Cooperative Learning Model To Improve Accounting Learning Outcomes Post Pandemic At Higher Education - listiadi, agung; Nikmah, Choirul (International Economic Conference of Business and Accounting, 2024)
In achieving success in the learning process in accordance with the curriculum, in learning activities not only the teacher plays a full role but vice versa. However, the teacher still plays an important role in the teaching and learning process, especially in the process of delivering material, therefore various learning methods start from lectures, demonstrations, and cooperatives. Based on cognitive learning theory, one of the learning models that can increase student interest, activity, and learning outcomes is the cooperative learning model. Of the various methods the author chose the Numbered Heads Together cooperative learning model so that it is expected to improve student learning outcomes, bearing in mind that this learning model has never been applied before. This research is a type of classroom action research with a Quantitative Descriptive method conducted in two cycles. The results showed that with the Numbered Heads Together cooperative learning model, student learning outcomes could be achieved in each cycle. Student responses to the application of the Numbered Heads Together (NHT) cooperative learning model in accounting learning were very positive. This can be seen from the students who are happy in following this whole lesson.